Point-of-care universal screening for meticillin-resistant Staphylococcus aureus: a cluster-randomized cross-over trial. Issue 3 (March 2017) - Wu, P.J.; Jeyaratnam, D.; Tosas, O.; Cooper, B.S.; French, G.L.
Summary: Background: Meticillin-resistant Staphylococcus aureus (MRSA) is frequently endemic in healthcare settings and may be transmitted by person-to-person spread. Asymptomatic MRSA carriers are potential, unsuspected sources for transmission and some of them may be identified by admission screening. Aim: To assess whether rapid point-of-care screening (POCS) for MRSA at hospital admission may be associated with a reduction in MRSA acquisition rates when compared with slower laboratory-based methods. Methods: A cluster-randomized cross-over trial was conducted in four admission wards of an acute London tertiary care hospital. Polymerase chain reaction-based POCS screening was compared with conventional culture screening. Patients were screened on ward admission and discharge, and the MRSA acquisition rate on the admission wards was calculated as the primary outcome measure. Results: In all, 10, 017 patients were included; 4978 in the control arm, 5039 in the POCS arm. The MRSA carriage rate on admission was 1.7%. POCS reduced the median reporting time from 40.4 to 3.7 h ( P  < 0.001). MRSA was acquired on the admission wards by 23 (0.46%) patients in the control arm and by 24 (0.48%) in the intervention arm, acquisition rates of 5.39 and 4.60 per 1000 days respectively. After taking account of predefined confounding factors, the adjusted incidence rate ratio (IRR) for change in trend for MRSA acquisition was 0.961 (95% confidence interval: 0.766–1.206). The adjusted IRR for step change for MRSA acquisition was 0.98 (0.304–3.162). Conclusion: POCS produces a significantly faster result but has no effect on MRSA acquisition on admission wards compared with culture screening. Where compliance with infection prevention and control is high and MRSA carriage is low, POCS has no additional impact on MRSA acquisition rates over the first one to four days of admission compared with conventional culture screening.